STASIONERITAS DAN KOINTEGRASI NILAI PASAR, NILAI BUKU DAN RESIDUAL INCOME UNTUK MENENTUKAN NILAI PERUSAHAAN: PENGUJIAN MODEL OHLSON (1995) - Suartana, I Wayan (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2005)
This paper investigates the time-series properties of the Ohlson (1995) model and examines their implications for empirical studies thet use time-series data. Time-series properties that examined is stationarity and cointegration. Based on a sample of 16 firms with complete quarterly data from 1990 to 2001, we show that alternative hypothesis that market value, book value and residual income are stationarity most of the sample firms. More importantly, book value and residual income cointegrate market value for 69 percent of sample firms.Keywords: Measurement Perspective, Model Ohlson, Stationarity, Cointegration.